Pemendekan Waktu ELISA dalam Deteksi TMV - Susamto Somowiyarjo; Y. B. Sumardiyono; Purwati Widiyati (Jurnal Perlindungan Tanaman Indonesia, 1996)
In order to support the program for the management of viral diseases on garlic, a rapid diagnosis procedure was developed by shortening the incubation period of the indirect ELISA. No significant differences of ELISA absorbance were observed when the antigen was incubated for 4 h, 2 h, and 30 min at 37ºC. The incubation period for the antibody and conjugate could he reduced from 4 h at 37ºC or 18 h at 4ºC to 30 min al 37ºC. The shortest period of incubation for the assay could be obtained when each incubation time for the antigen, antibody and conjugate was 30 min. The detection limit for the shortened ELISA was 10^-4 for the virus in crude extracts and 0,5 μg/ml for the purified preparation.